Assessing the negative impacts of unconventional monetary policies: Zombie companies in the Finnish economy - Pihlajamaa, Matias Samuel (My University, 2020)
Euro-area inflation has not been able to reach the targeted sub-two percentage level which has led to the implementation of a wide range of monetary tools and policies. Conventional tools, to which this paper refers to as tools that are included in the original mandate of the European Central bank (henceforth ECB), have not had the desired impact on the economy and the euro- area inflation. The new tools, such as forward guidance, quantitative easing, and negative interest rate policies have affected positively the economy, but albeit the growing volume of the new measures the inflation level has not reached the ECB's target level. At the same time, the unconventional pol- icies have gained increasing criticism due to their negative side-effects. Most notably, the critics have claimed that the policies jeopardize financial stability and create a moral hazard because negative interest rates have forced the financial institutions to seek yields from riskier asset classes. Furthermore, the increasing liquidity in the economy has raised concerns about the growing number of zombie companies that have not exited the market due to the low-interest rate levels and market inefficiencies. Global results present that zombie companies lower the overall efficiency by building bottlenecks by inefficient capital allocation and hinder new market entries and innovations. The purpose of this thesis is to estimate the number of zombie compa- nies in the Finnish economy utilizing listed company data and scrutinize the negative impact of said companies. The most significant contribution of this paper is the broad estimates of zombie companies in the Finnish economy with methods that are for not better knowledge utilized in the Finnish data sample before. Broad zombie company estimates in line with previous academia utilizing listed company data from the Finnish economy provide insight into the phenomena in the Finnish economy. Esti- mates define 11-28 companies to be zombies from the data sample. The results present that in particular, in the mining and computer- and software service industries the number of zombie companies is more prominent than in others. The results also indicate that the financial industry is not well suited for these kinds of estimates due to the reason that the character of the industry is large debt ratios.

Euroopan keskuspankki (EKP) ei ole kyennyt saavuttamaan tavoiteltua liki kahden prosenttiyksi- kön vuosittaista inflaatiotavoitetta monipuolisesta rahoituspolitiikan käytöstä huolimatta. Tämä tutkimus viittaa tavanomaisina työkaluina EKP:n alkuperäisen mandaatin määrittelemiin raha- poliittisiin työkaluihin, joista ei ole ollut toivottua vaikutusta talouteen tai euroalueen inflaati- oon. Rahapolitiikan epätavanomaiset työkalut ja operaatioiden kasvavat suuruusluokat ovat vaikut- taneet euroalueen talouteen positiivisesti, mutta inflaatiotavoitteeseen ei olla näistä toimista huolimatta päästy. Uusia työkaluja ovat ennakoiva viestintä rahapolitiikan vaikutuksista, mää- rällinen kevennys, sekä negatiivinen korkopolitiikka. Kriitikot väittävät epätavanomaisen raha- politiikan vaarantavan talouden tasapainon luomalla moraalikatoa, jonka seurauksena rahoi- tusinstituutiot pakotetaan hakemaan tuottoa enemmän riskejä sisältävistä omaisuusluokista. Li- säksi talouden kasvanut likviditeetti on nostanut huolia zombiyritysten kasvavasta määrästä, jotka eivät ole poistuneet markkinoilta alhaisen korkoympäristön ja markkinoiden toimimatto- muuden johdosta. Kansainväliset tutkimukset osoittavat, että zombiyritykset laskevat kansanta- louden kokonaistuottavuutta luomalla pullonkauloja uusille toimijoille ja näin vähentäen inno- vaatiotoimintaa. Tämän tutkimuksen tavoitteena on estimoida zombiyritysten lukumäärää Suo- messa hyödyntämällä listattujen yritysten dataa ja arvioimalla näiden yritysten haitallisia vaiku- tuksia taloudessa. Tämän tutkimuksen tärkeimpänä kontribuutiona ovat laajat zombiyritysten lukumäärää estimoivat estimaatit, joita ei ole paremman tietämyksen valossa aikaisemmin hyö- dynnetty suomalaisessa data-aineistossa. Laajat estimaatit, jotka ovat linjassa kansainvälisten empiiristen tutkimusten kanssa antavat os- viittaa zombiyritysten lukumäärästä Suomessa. Estimaatit osoittavat, että 11-28 yritystä voidaan määritellä zombeiksi käytetyn datan nojalla. Saadut tulokset viittaavat siihen, että erityisesti kai- vosteollisuus ja tietokone- ja ohjelmistojenhuoltotoimiala ovat haavoittuvaisia zombiyrityksille käytettyjen estimaattien perusteella. Tämän lisäksi tulokset näyttävät, että rahoitustoimiala ei sovellu käytettyihin estimaatteihin, koska korkea velkaantuneisuusaste kuuluu toimialan erikois- piirteisiin.
Keywords: economics; monetary policy; inflation (economics); fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|